Analisis Akuntansi Syariah dan Good Governance pada Lembaga Keuangan Mikro Syariah - Norasyikin Norasyikin; Guslinawati Guslinawati; Wira Hubaya Umista; Aslina Aslina (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to explore how the implementation of Islamic accounting strengthens good governance practices in Islamic Microfinance Institutions. The research employs a qualitative methodology with a case study approach, utilizing in-depth interviews, observations, and document analysis for data collection. Thematic analysis is conducted to identify patterns and meanings related to the application of Islamic accounting principles and good governance within the institution. The findings reveal that Islamic accounting, which emphasizes honesty, justice, and social responsibility, plays a crucial role in supporting transparency and accountability, thereby enhancing member trust and institutional sustainability. However, the effectiveness of Islamic accounting implementation largely depends on the competence of human resources and adequate managerial support.